2017
DOI: 10.1016/j.ejor.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Default and liquidation timing under asymmetric information

Abstract: We consider a dynamic model in which shareholders delegate a manager, who observes private information about running and liquidation costs of the firm, to operate the firm. We analytically derive the shareholders' optimal contract contingent on the cost structure of the firm. The information asymmetries change the high-cost firm's default and liquidation timing. Even if the liquidation value is higher than the face value of debt, the shareholders of the high-cost firm, unlike in the symmetric information case,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
(87 reference statements)
0
17
0
Order By: Relevance
“…Following Mella- Barral and Perraudin (1997), Lambrecht and Myers (2008), Nishihara and Shibata (2017), and Nishihara and Shibata (2018), we consider the following two types of the firm's exit. A successful exit without formal bankruptcy is called sell-out.…”
Section: Exit Choice Between Sell-out and Defaultmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Mella- Barral and Perraudin (1997), Lambrecht and Myers (2008), Nishihara and Shibata (2017), and Nishihara and Shibata (2018), we consider the following two types of the firm's exit. A successful exit without formal bankruptcy is called sell-out.…”
Section: Exit Choice Between Sell-out and Defaultmentioning
confidence: 99%
“…Shareholders receive the residual value (i.e., the sales price minus C/r). For simplicity, as in Lambrecht and Myers (2008), Nishihara and Shibata (2017), and Nishihara and Shibata (2018), we assume no opportunity for debt renegotiation and…”
Section: Exit Choice Between Sell-out and Defaultmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouvard (2014) proposes a signaling model to reveal the value of an investment project via sequential investments, thus initiating a learning phase where outside investors can update their beliefs on the probability of holding a high quality project. Besides capital financing, real options signaling game models have been adopted to analyze various corporate finance issues, like liquidation timing of a distressed firm (Nishihara and Shibata, 2017), strategic investment games of incumbent and entrant firms (Watanabe, 2016), decisions on selling out IPO (Nishihara, 2016), mergers and acquisitions strategies of bidder and target firms (Leung and Kwok, 2018). A comprehensive and general review of signaling theory can be found in Connelly et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bouvard (2014) proposes a signaling model to reveal the value of an investment project via sequential investments, thus initiating a learning phase where outside investors can update their beliefs on the probability of holding a high quality project. Besides capital financing, real options signaling game models have been adopted to analyze various corporate finance issues, like liquidation timing of a distressed firm (Nishihara and Shibata, 2017), strategic investment games of incumbent and entrant firms (Watanabe, 2016), decisions on selling out IPO (Nishihara, 2016), mergers and acquisitions strategies of bidder and target firms (Leung and Kwok, 2018). A comprehensive and general review of signaling theory can be found in Connelly et al (2011).…”
Section: Introductionmentioning
confidence: 99%